WASTE, BOREDOM, AND GHOSTLY TIME IN THE FILMS OF TSAI MING-LIANG - Watkins, Raymond (Animus. Revista Interamericana de Comunicação Midiática, 2021)
This study examines several themes that often emerge in the work of Taiwanese filmmaker Tsai Ming-liang, focusing on his preoccupation with waste, boredom, and a secret, “ghostly” time that runs parallel to human time. While comparisons are inevitably drawn to the French New Wave in terms of attitudes toward modernity, I argue that Tsai develops a much different tone. While the French New Wave might best be characterized by freshness, naivieté, improvisation, playfulness, and a sense of possibility, then Tsai instead offers a much more bleak, post-apocalyptic world in which the consequences of advanced modernity now become a heavy burden on his characters.